2003
DOI: 10.1021/jf025916z
|View full text |Cite
|
Sign up to set email alerts
|

Apple Peels as a Value-Added Food Ingredient

Abstract: There is some evidence that chronic diseases, such as cancer and cardiovascular disease, may occur as a result of oxidative stress. Apple peels have high concentrations of phenolic compounds and may assist in the prevention of chronic diseases. Millions of pounds of waste apple peels are generated in the production of applesauce and canned apples in New York State each year. We proposed that a valuable food ingredient could be made using the peels of these apples if they could be dried and ground to a powder w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
208
4
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 355 publications
(229 citation statements)
references
References 35 publications
12
208
4
5
Order By: Relevance
“…Due to large quantity of produced apple pomace, the preparation of single product would not be economically feasible and production of alternative products should be explored. Million pounds of waste apple peels are also generated in apples industry each year (Wolfe and Liu, 2003), with high costs of disposal and threat to the environment. Several studies focused on apple peel properties, due its high content of phenolic compounds and antioxidants.…”
Section: Vegetable and Fruitsmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to large quantity of produced apple pomace, the preparation of single product would not be economically feasible and production of alternative products should be explored. Million pounds of waste apple peels are also generated in apples industry each year (Wolfe and Liu, 2003), with high costs of disposal and threat to the environment. Several studies focused on apple peel properties, due its high content of phenolic compounds and antioxidants.…”
Section: Vegetable and Fruitsmentioning
confidence: 99%
“…High concentrations of phenolic compounds in apple peels may support the prevention of chronic diseases, such as cardiovascular diseases and cancer. In their review, Wolfe and Liu (2003), stated that valuable food ingredient could be made using the waste peels, trough drying and grounding processes without large losses of phytochemicals. Rome Beauty apple peels were treated with citric acid dips, ascorbic acid dips, and blanches and dried under various conditions.…”
Section: Vegetable and Fruitsmentioning
confidence: 99%
See 1 more Smart Citation
“…Also Jaros et al [41] marked the content of polyphenolic compounds from different varieties of apples, in the range of 585-655 mg/L. According to Wolfe and Lui [47], the content of polyphenolic compounds in apple juices can affect the maturity and the variety of used fruit and to the greatest extent is shaped by the production process [7]. During the production of apple juice, a part of polyphenolic compounds undergo the process of enzymatic oxidation to quinones.…”
Section: Quantitative Analysismentioning
confidence: 99%
“…Citrus fiber is of high quality when compared to other forms of dietary fiber, due to the presence of associated bioactive compounds, such as flavonoids and other polyphenols, and carotenoids (Fernández-Ginés et al, 2003;Wolfe, Liu, 2003). Some studies have demonstrated the importance of the recovery of orange processing byproducts to obtain beneficial substances for the body, especially the gastrointestinal tract.…”
Section: Introductionmentioning
confidence: 99%